Korelasi antara Kepemimpinan Kepala Sekolah dan Supervisi Akademik terhadap Kinerja Guru Sekolah Dasar di Kecamatan Lebakgedong Kabupaten Lebak - Luna Starlinsky; Tian Belawati; Tita Rosita (Indonesian Journal of Educational Counseling, 2022)
CORRELATION BETWEEN PRINCIPAL LEADERSHIP AND ACADEMIC SUPERVISION ON ELEMENTARY SCHOOL TEACHER PERFORMANCE IN LEBAKGEDONG DISTRICT, LEBAK REGENCY. The low performance is one of the key factors affecting student success. Teachers are expected to meet and materialize stakeholders’ hopes and needs in helping students achieving the learning goals. Literatures have shown that teacher’s performance is also affected by many factors, among others are the leaderships of the school principal and the academic supervision offered by the school principal. This paper reports the findings of a study that was intended to see the correlation between school principal leaderships and academic supervision with teacher performance. The study is quantitative research from 64 teachers sample in an Elementary School in Lebakgedong, Lebak Regency. Data was collected through Likert-scale questionnaires and was analyzed using Chi square test. The result show that both the principal leadership (X1) and academic supervision (X2) have positive significant relationships with teacher performance (Y), partially and simultaneously.